2017
DOI: 10.1186/s13690-017-0210-z
|View full text |Cite
|
Sign up to set email alerts
|

A population-based survey on physical inactivity and leisure time physical activity among adults in Chiang Mai, Thailand, 2014

Abstract: BackgroundReducing physical inactivity among the population is a challenge for many nations. Targeting leisure time physical activity (LTPA) may be useful in increasing overall physical activity as it is assumed it is associated with a higher degree of free choice and personal preference than physical activity at work and during travel. The study explored the prevalence of physical inactivity and focused on the overall level of energy expenditure and energy level spent during leisure time among those who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
(40 reference statements)
3
27
1
Order By: Relevance
“…Leisure-time activity accounted for the second-largest proportion of physical activity composition in 2013. These results were inconsistent with those of previous studies of middle-income and developing countries in Asia that reported very little contribution of leisure-time activity to the overall physical activity 23 , 26 , 33 , 34 ) , while the dominance of leisure-time physical activity is common in developed countries 35 ) . Employee workers were more likely to engage in leisure physical activity than were self-employed workers in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Leisure-time activity accounted for the second-largest proportion of physical activity composition in 2013. These results were inconsistent with those of previous studies of middle-income and developing countries in Asia that reported very little contribution of leisure-time activity to the overall physical activity 23 , 26 , 33 , 34 ) , while the dominance of leisure-time physical activity is common in developed countries 35 ) . Employee workers were more likely to engage in leisure physical activity than were self-employed workers in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The proportion of low-level physical activity among Mongolian adults, 10.9% in 2005 and 27.2% in 2013, was similar to that in a study from Thailand, which reported a proportion of 26.0% in 2014 23 ) and lower than those reported in studies from Bangladesh 24 ) , India 25 ) , and Vietnam 21 , 26 ) . Physical activity time of Mongolian adults was similar to the study from Vietnam 21 ) and longer than those of Bangladesh 24 ) , India 25 ) .…”
Section: Discussionsupporting
confidence: 79%
“…Our results showed that the prevalence of physical inactivity was higher than previously reported in other countries. In Americas, 5 Brazil, 6 Thailand 19 and Mexico, 20 the prevalence of physical inactivity was 43.3%, 41.1%, 26.0% and 19.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 21 24 30 To our knowledge, physical inactivity is more common in women than in men in most countries. 19 We did the gender–covariate interactions tests to explore whether there were different risk factors among men and women, and found that smoking cigarettes and drinking alcohol were significantly associated with physical inactivity level in men but not in women. The possible reason for this finding may be that the proportion of women who smoked cigarettes and drank alcohol in China was relatively lower than men.…”
Section: Discussionmentioning
confidence: 99%
“…The GPAQ was considered as a valid and reliable instrument in assessing PA compared to accelerometer and the International Physical Activity Questionnaire (IPAQ) [ 26 , 27 ]. The GPAQ was available in Thai version and widely used for population based surveys in Thailand [ 28 , 29 ]. The prevalence of PA was calculated by dividing the number of participants who met the recommended aerobic PA levels (at least 150 min/week of moderate-intensity aerobic PA or 75 min/week of vigorous-intensity aerobic PA or an equivalent combination of moderate- and vigorous-intensity aerobic PA) [ 30 ] by the total number of participants.…”
Section: Methodsmentioning
confidence: 99%